Dynamics of the gas-plasma torch formed by the highcurrent electron beam action on solid targets - Klepikov, V.F.; Lytvynenko, V.V.; Lonin, Yu.F.; Ponomarev, A.G.; Tolstolutskiy, O.G.; Uvarov, V.V.; Uvarov, V.T. (Вопросы атомной науки и техники, 2009)
The interaction of high-current REВ with the surface of solid targets was investigated. The target material was stainless steel 12Х18Н10Т, graphite, tungsten, plexiglas. The optical diagnostic methods were used to determine the space-time characteristics of a gas-plasma torch (GPT), formed as a result of the tubular microsecond REB action on the surface of solid targets. The times of GPT formation and its spread velocity (transverse and longitudinal) for different materials were determined. An axial focus of GPT, moving towards the beam, was found.